Development of Monoclonal Antibodies and Antigen-Capture ELISA for Human Parechovirus Type 3 - Keiko Goto; Yutaro Yamaoka; Hajera Khatun; Kei Miyakawa; Mayuko Nishi; Noriko Nagata; Toshikazu Yanaoka; Hirokazu Kimura; Akihide Ryo (Microorganisms, 2020)
Human parechovirus type 3 (HPeV3) is an etiologic agent of respiratory diseases, meningitis, and sepsis-like illness in both infants and adults. Monoclonal antibodies (mAbs) can be a promising diagnostic tool for antigenic diseases such as virus infection, as they offer a high specificity toward a specific viral antigen. However, to date, there is no specific mAb available for the diagnosis of HPeV3 infection. In this study, we developed and characterized mAbs specific for HPeV3 capsid protein VP0. We used cell-free, wheat germ-synthesized viral VP0 protein for immunizing BALB/c mice to generate hybridomas. From the resultant hybridoma clones, we selected nine clones producing mAbs reactive to the HPeV3-VP0 antigen, based on enzyme-linked immunosorbent assay (ELISA). Epitope mapping showed that these mAbs recognized three distinct domains in HPeV3 VP0. Six mAbs recognized HPeV3 specifically and the other three mAbs showed cross-reactivity with other HPeVs. Using the HPeV3-specific mAbs, we then developed an ELISA for viral antigen detection that could be reliably used for laboratory diagnosis of HPeV3. This ELISA system exhibited no cross-reactivity with other related viruses. Our newly developed mAbs would, thus, provide a useful set of tools for future research and ensure HPeV3-specific diagnosis.